Implementasi Konsep Manajemen Pendidikan dalam Surat Luqman Ayat 13-19: Studi Kasus di SMAN 1 Solok - Aris, Maifalinda; Bustamam, Risman; Junaidi, Junaidi; Febrina, Winda; Nengsih, Dona (Indo-MathEdu Intellectuals Journal, 2024)
This study examines the implementation of the values contained in Surat Luqman verses 13-19 in education management at SMAN 1 Solok, Indonesia. Through a qualitative approach involving observation, interviews, and analysis of documents, the study explores how these values are integrated into school policies and practices. Data analysis was carried out qualitatively consisting of data reduction, data presentation, and conclusion drawn. The results of the study show that the integration of Islamic values contributes significantly to the development of students' character, the increase of teachers' pedagogical capacity, and the strengthening of parental involvement. Despite facing challenges such as lack of resources and diversity of student backgrounds, SMAN 1 Solok has managed to implement these values effectively through the development of adaptive educational materials, inclusive educational approaches, and strengthened teacher training programs. This study emphasizes the importance of a holistic approach in education that focuses not only on academic achievement but also on the formation of students' morals and ethics